Dock Square, ca. 1867 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southeast from Washington Street toward Dock Square and Faneuil Hall. Many of the buildings have business signage affixed and horse-drawn vehicles are seen in the street. Note the tracks for the horse railway which run down Washington Street into Dock Square. 12 1/2 x 9 7/8 Photographs